Environmental Activism: Analyzing the Attitudes of Eco-Friendly Consumers - Martono, S; Prajanti, Sucihatiningsih Dian Wisika; Yulianto, Arief; Wijaya, Angga Pandu; Dwiningrum, Siti Irene Astuti (Journal of Ecohumanism, 2024)
This study aims to examine the influence of environmental knowledge and environmental concern on environmental attitude and environmental activism. Environmental degradation, caused by various factors, is a critical issue that necessitates investigation. Knowledge is an essential aspect, while environmental concern represents the willingness to take action. This research employs a quantitative approach to test these variables with a sample size of 259 individuals who are environmentally conscious and engage in eco-friendly activities, both personally and through campaigns. Data were collected using a questionnaire administered to the Indonesian public, who generally require greater literacy on environmental sustainability. The results indicate that environmental knowledge significantly impacts environmental attitude and environmental activism. These findings underscore the importance of education and campaigns in providing understanding and achieving widespread impact. The study also reveals that environmental concern contributes to fostering care and environmental activism. The implications of this research highlight the need to enhance conservation campaigns and education to increase public awareness of environmental issues and encourage the application of this understanding in everyday practices.